Toward Educational Transformation: Three Educators' Experiences With Critical Pedagogy Across Disciplines - Moyo, Nozipho; Rabalais, Caroline B; Ahmed, Ahmed (Journal of language & literacy education, 2024)
Literacy learning holds infinite possibilities for empowering and transforming students of all levels through the power of language. However, there are barriers to these possibilities that limit the agency teachers should possess in their classrooms, such as curricular mandates, high-stakes standardized testing, and even surveillance. These challenges can prevent teachers from embracing students' many ways of being, knowing, and speaking to promote many harmful ideologies and restrict their learning. Critical pedagogy creates a pathway to push back against these barriers. Through narrative inquiry, three literacy educators across different subjects, namely the English language arts, English as a second language, and the Arabic language and culture classroom, come together to interrogate how they incorporate critical pedagogy in their classrooms for the purpose of educational transformation. Findings suggest that student engagement with identity, community, and equity increases when opposing restrictive educational expectations. This article has implications for practicing educators in the K-16 space to take on critical pedagogies in their own contexts despite increasing barriers to justice-oriented teaching.